Decreasing lifetime prevalence of diabetes-related foot ulcers in Norway: repeated cross-sectional population-based surveys from the HUNT study (1995-2019) - Riise, Hilde K. R.; Igland, Jannicke; Graue, Marit; Haugstvedt, Anne; Østbye, Truls; Søfteland, Eirik; Hermann, Monica; Carlsson, Sofia; Åsvold, Bjørn Olav; Iversen, Marjolein M. (Frontiers in Endocrinology, 2024)
Background and aims: Diabetes-related foot ulcers (DFU) are a persistent healthcare challenge, impacting both patients and healthcare systems, with adverse effects on quality of life and productivity. Our primary aim was to examine the trends in lifetime prevalence of DFU, as well as other micro- and macrovascular complications in the Trøndelag Health Study (HUNT) in Norway. Methods: This study consists of individuals ≥20 years with diabetes participating in the population-based cross-sectional HUNT surveys (1995-2019). Prevalence ratios, comparing the lifetime prevalence of DFU and other relevant micro- and macrovascular complications between the HUNT surveys, were calculated using Poisson regression. Results: The lifetime prevalence (95% confidence interval (CI)) of a DFU requiring three or more weeks to heal was 11.0% (9.5-12.7) in HUNT2, 7.5% (6.3-8.8) in HUNT3 and 5.3% (4.4-6.3) in HUNT4. The decrease in DFU prevalence from 1995 to 2019 was observed in both men and women, for all age groups, and for both type 1 and type 2 diabetes. The highest lifetime prevalence of DFU was found among those with type 1 diabetes. The decrease in HbA1c from HUNT2 to HUNT4 did not differ between those with and without a DFU. The prevalence of chronic kidney disease (eGFR <60 mL/min/1.73m2 (eGFR categories G3-G5)) increased in both individuals with and without a DFU. Conclusion: Results from the HUNT surveys show a substantial decline in the lifetime prevalence of DFU from 1995 to 2019.